Tribological behavior of lubricant-impregnated porous polyimide - Jinbang Li; Ningning Zhou; Janet S. S. Wong (Friction)
Abstract Porous materials impregnated with lubricants can be used in conditions where limited lubricant is desirable. In this work, three porous polyimides (PPI) with different densities were prepared. Polyalphaolefin (PAO) impregnated PPI (iPPI) discs were rubbed against steel and sapphire balls. In operando observations of the iPPI–sapphire contacts show that oil is released under an applied load, forming a meniscus around contacts. Cavitation at the outlet is created at high sliding speeds. The amount of released oil increases with increasing PPI porosity. Contact moduli, E*, estimated based on the actual contact size show that trapped oil in iPPIs contributes to load support. At higher speeds, tribological rehydration of the contact occurs in low density iPPI, with that E* rises with speed. For high density PPIs, high speeds give a constantly high E* which is limited by the viscoelastic properties of the PPI network and possibly the rate of oil exudation. Friction of iPPI–steel contacts is governed by the mechanical properties of the PPI, the flow of the lubricant, and the roughness of the PPI surfaces. For low- and medium- density (highly porous, high roughness) PPIs, large amount of oil is released, and lubrication is mainly via lubricant restricted in the contact in the pores and possibly tribological rehydration. For high density (low porosity) PPI, with lower roughness, hydrodynamic lubrication is achieved which gives the lowest friction. Our results show that polymeric porous materials for effective lubrication require the optimization of its surface roughness, stiffness, oil flow, and oil retentions.